A low-phase-noise 18-GHz-band frequency synthesizer with low frequency step size - Biglarbegian, B.; Hodjat Kashani, F.; Ameri Mahabadi, H. (2006)
Due to development of both wireless communication users and communication line users, utilization of high-speed communications has become a vital essence. High speed digital microwave radios have a great contribution in wireless telecommunications. Having a different and high capacitance, these radios can transmit and receive data in point to point links in far distances up to 30 km. Considering the high rate of utilization such digital microwave radios have in lower bands, it is imperative to utilize such kind of radios in upper bandsfor accessing more channels. One of the radios that plays a significant role in communications is digital microwave radio 18 GHz. Through using a proper modulation in this band, transmitting data with high rate is achievable. In this paper, frequency synthesizer of this radio has been analyzed, designed and implemented. By applying proper changes, this synthesizer can be used as a frequency sweeper either. In this project in order to have a stable local oscillator and a good phase noise of output signal, a phase locked DRO was designed and implemented. This stable signal will be mixed with an L-band synthesized signal and it will generate signal in the band 17.7 GHz -19.7 GHz with step 0.25 MHz. The stable output signal of this synthesizer has a very good phase noise at 18 GHz. We have achieved to phase noise up to -88 dBc/Hz @10 kHz in 18 GHz which is a proper phase noise for using different modulations such as QPSK, 16QAM, 64QAM and...